The Influence of Teacher and Parent Cooperation in Improving the Learning Process in High Schools in Economics Lessons - Aprizal; Paulus Djohan Lolo (LPPM Undiksha, 2025)
This study highlights the importance of parental involvement in the educational process of students, which is often hampered by social and economic disparities. The urgency of this study arises from the differences of opinion regarding the role of parents in education, which need to be explored to improve understanding and practice of collaboration between schools and parents. The purpose of the study was to analyze the background of parents and the cooperative relationship between schools and parents in improving education in high schools, especially in economic education. The research method used is quantitative with a survey approach. The research population was all high school students in the city of Makassar, with a sample of 740 students taken randomly. Data collection techniques were carried out through questionnaires designed to measure various indicators related to parental background, school cooperation, and parental involvement. Data analysis techniques using SPSS Version 29.0 assess the mean, percentage and interpret the data. The results showed a significant relationship between school and parental cooperation in improving student education. The findings revealed that the greater the school's appreciation for the arrival of parents, the higher the parental involvement in student education. The conclusion is that parental background has a significant effect on the quality of student education. The implications of the study direct schools to strengthen collaborative programs with parents and provide training that can support their involvement. Research suggestions, a comprehensive approach to gain a deeper perspective on parents' experiences in supporting students.